High Activation of γδ T Cells and the γδ2pos T-Cell Subset Is Associated With the Onset of Tuberculosis-Associated Immune Reconstitution Inflammatory Syndrome, ANRS 12153 CAPRI NK - Pean, Polidy; Nouhin, Janin; Ratana, Meng; Madec, Yoann; Borand, Laurence; Marcy, Olivier; Laureillard, Didier; Fernandez, Marcelo; Barré-Sinoussi, Françoise; Weiss, Laurence; Scott-Algara, Daniel (Frontiers in Immunology, 2019)
Background: Human Immunodeficiency Virus 1 (HIV-1) and Mycobacterium Tuberculosis (Mtb) co-infected patients are commonly at risk of immune reconstitution inflammatory syndrome (IRIS) when initiating antiretroviral treatment (ART). Evidence indicates that innate immunity plays a role in TB-IRIS. Here, we evaluate the phenotype of Gamma-delta (γδ) T cells and invariant Natural Killer (iNK) T cells in tuberculosis-associated IRIS. Methods: Forty-eight HIV+/TB+ patients (21 IRIS) and three control groups: HIV–/TB– (HD, n = 11), HIV+/TB– (n = 26), and HIV–/TB+ (n = 22) were studied. Samples were taken at ART initiation (week 2 of anti-tuberculosis treatment) and at the diagnosis of IRIS for HIV+/TB+; before ART for HIV+/TB-, and at week 2 of anti-tuberculosis treatment for HIV–/TB+ patients. γδ T cells and Invariant natural killer T (iNKT) cells were analyzed by flow cytometry. Results: Before ART, IRIS, and non-IRIS patients showed a similar proportion of γδpos T and iNKT cells. HLA-DR on γδpos T cells and δ2posγδpos T cells was significantly higher in TB-IRIS vs. non-IRIS patients and controls (p < 0.0001). NKG2D expression on γδpos T cells and the δ2posγδpos T cell subset was lower in HIV+/TB+ patients than controls. CD158a expression on γδpos T cells was higher in TB-IRIS than non-IRIS (p = 0.02), HIV+/TB–, and HIV–/TB- patients. Conclusion: The higher activation of γδposT cells and the γδ2posγδpos T cell subset suggests that γδ T cells may play a role in the pathogenesis of TB-IRIS.